Respuesta :

we have the expression

[tex]\frac{4}{3x^2-23x+40}[/tex]

Rewrite as equivalent rational expressions with denominator (3x-8)(x-5)(x-3)

In this problem

3x^2-23x+40=3(x-5)(3x-8)

so

[tex]\frac{4}{3x^2-23x+40}=\frac{4}{3\mleft(x-5\mright)\mleft(3x-8\mright)}[/tex]

Multiply by (x-3)/(x-3)

[tex]\frac{4}{3(x-5)(3x-8)}\cdot\frac{(x-3)}{(x-3)}=\frac{4(x-3)}{3(x-5)(3x-8)(x-3)}[/tex]

Part 2

we have the expression

[tex]\frac{9x}{3x^2-17x+24}[/tex]

we have that

3x^2-17x+24=3(3x-8)(x-3)

so

[tex]\frac{9x}{3x^2-17x+24}=\frac{9x}{3\mleft(3x-8\mright)\mleft(x-3\mright)}=\frac{3x}{(3x-8)(x-3)}[/tex]

Multiply the expression by (x-5)/(x-5)

[tex]\frac{3x}{(3x-8)(x-3)}\cdot\frac{(x-5)}{(x-5)}=\frac{3x(x-5)}{(3x-8)(x-3)(x-5)}[/tex]